(untitled) (MCIT: Proceedings of International scientific and practical conference, 2019)
A mathematical model of the electrocoagulation process has been constructed, taking into account the geometric dimensions of the reactor, the volumetric flow rate of the liquid and the applied current. A simulation model has been developed that describes the processes occurring in a coagulator, on the basis of which was studied the influence of current, changes in the concentration of inlet contamination on the concentration of the target component at the outlet of the reactor.